(untitled) (Research, Society and Development, 2021)
Brazil has a long history of using medicinal plants in the treatment of health problems in the population, a use based on experience and disseminated by orality and experience, being widely used until the mid-twentieth century. Allium sativum L. is one of the oldest medicines in the world. For its diverse biological activities. In Allium sativum L. allicin resulting from the action of the enzyme allinase together with allin after crushing the garlic bulb is found. In addition to allicin, the garlic extract has as secondary metabolites, alkaloids, saponins, tannins, terpenes and flavonoids, which may be susceptible to antimicrobial activity. An integrative literature review was carried out, with searches of individual scientific documents in the databases as well as: Scielo, Medline (PubMed), Lilacs, Scopus, ScienceDirect, Capes Periodicals and in scientific repositories, as a criterion for inclusion of documents of a nature scientific, in Portuguese, English and Spanish, which presented a relation of the antimicrobial potential of Allium sativum L. Therefore, the research aimed to show the main metabolites from Allium sativum L. and to verify their response and report the agreement of different studies in relation to the potential of Allium sativum L., the antimicrobial and fungal properties against gram positive and gram-negative bacteria and fungi, involving a literature review.